PSYCHOEDUCATION TO PREVENT SMARTPHONE ADDICTION THROUGH COMMUNITY BASED INTERVENTION - Puspasari, Karisma Dewi (Universitas Muhammadiyah Lampung, 2025)
The prevalence of problematic smartphone usage has become a widespread concern. Excessive smartphone use can develop into an addiction if prompt intervention is not implemented. In order to effectively engage a broader demographic, health cadres play a crucial role in disseminating information to parents regarding strategies for mitigating smartphone addiction in children. The study aimed to examine the effect of psychoeducational interventions to prevent smartphone addiction among children in health cadres. The study employed a quasi-experimental, one-group pre-test and post-test design. The questionnaire comprised ten questions with a reliability coefficient of 0.60. Twenty health cadres from Public Health Center X in Malang were selected as participants. A series of six sessions were done to provide psychoeducation to prevent smartphone addiction. The findings revealed a discernible disparity between the scores obtained before the intervention's implementation and those obtained after completion. The t-test analysis revealed a statistically significant difference between the pre-test and post-test scores, as shown by a significance level of p < 0.001 and a t-value of -9.787. This finding suggests that the intervention increased the knowledge of the health cadres.